The Management of Resistant Hypercalcaemia Secondary to Cancer of Unknown Primary and Presenting with Pancreatitis - Jayan George (Reports, 2019)
We present a 31-year-old female who presented to the general surgical take with epigastric pain associated with a raised amylase and corrected calcium on admission. Computed tomography confirmed acute pancreatitis and also demonstrated a 15 cm liver tumour. She was subsequently diagnosed with cancer of unknown primary with liver metastases. The patient’s pancreatitis symptoms improved with conservative management, but her calcium proved quite resistant to basic measures. Further input was sought from the medical on-call endocrinology and oncology teams to help manage this patient’s hypercalcaemia, which included pamidronate, zolendronate, and denusomab, but ultimately it only improved significantly following chemotherapy. This case to our knowledge is the only one of its kind and highlights the importance of early multidisciplinary team involvement across specialties to help manage complex patients.